Increase of capacity and controlability of alternating current power transmission lines - Postolatii V.M.; Bicova E.V.; Timashova L.; Shakarian Iu. (Problems of the Regional Energetics)
The basic characteristics and economic parameters of electricity transmissions of new type - controlled self-compensating high-voltage lines (CSHVL) are stated. Advantages of the given type of electricity transmissions in comparison with traditional consist in the increased throughput and deep regulating in regime parameters and characteristics. These advantages are reached due to a new design, application of a complex of the equipment – phase shifting and compensating devices and the appropriate control systems. By the principles of work and regime parameters the given electricity transmissions concern to a category of controlled flexible systems of transfer of the electric power of an alternating current (Controlled Flexible Alternating Current Transmission Systems – CFACTS).